Apresiasi dan Pembelajaran Unsur Intrinsik Teks Drama Mahkamah Siswa Kelas XI SMA - Rafika Aini; Sudirman Shomary (Sajak: Jurnal Penelitian dan Pengabdian Sastra, Bahasa, dan Pendidikan, 2023)
This study aims to obtain information and data about the abilities and learning of students at SMA Negeri 1 Pekanbaru. The population in this study were 71 class XI students at SMA Negeri 1 Pekanbaru. The sample used is a purposive sample. The method used is descriptive method and quantitative approach. The techniques used are test techniques, interviews and observation. The test results from the research with an average score of 91.54 are in the very good category and the learning is in the very good category. After conducting a quantitative analysis of the research data regarding the ability to appreciate the intrinsic elements of the drama text "The Court" which includes themes, plots, characterizations/characters, dialogues and settings (backgrounds) of class XI students at SMA Negeri 1 Pekanbaru in the form of multiple choice of 10 questions and learning to appreciate the intrinsic elements of the drama text "Court" at Pekanbaru 1 Public High School, it can be concluded from the results of the study, namely the ability to appreciate the intrinsic elements of drama texts for class XI students at Pekanbaru 1 Public High School is very good, with an average score of 91.54 out of 71 students . Learning to appreciate the intrinsic elements of the drama text "Mahkamah" conducted by Indonesian language teachers at Pekanbaru 1 Public High School at the planning, implementation, and evaluation stages has been carried out very well.